Expression and functional role of β3‐adrenoceptors in the human ureter. (29th January 2013) - Matsumoto, Rikiya; Otsuka, Atsushi; Suzuki, Takahisa; Shinbo, Hitoshi; Mizuno, Takuji; Kurita, Yutaka; Mugiya, Soichi; Ozono, Seiichiro
<x xml:space="preserve">Abstract</x> Objectives To investigate the presence of β‐adrenoceptor subtypes in the human ureter, and to examine whether β3‐adrenoceptors modulate relaxation of the human ureter. Methods Expression of messenger ribonucleic acid of β‐adrenoceptors in the human ureter was determined by reverse transcription polymerase chain reaction, and distribution of β‐adrenoceptors was examined by immunohistochemistry. In functional studies, the relaxant effects of isoproterenol, procaterol, TRK‐380, salbutamol and BRL 37344 on KCl‐induced contraction of the human ureter were evaluated, and the inhibitory effects of isoproterenol, procaterol and TRK‐380 on electrical field stimulation‐induced contractions were determined. Results Expression of β1‐, β2‐ and β3‐adrenoceptor messenger ribonucleic acid in the human ureter was confirmed by reverse transcription polymerase chain reaction. Positive staining for β1‐, β2‐ and β3‐adrenoceptor was identified not only in smooth muscle, but also in the urothelium of the human ureter. All β‐adrenoceptor agonists decreased the tone of KCl‐induced contractions of the human ureter with a rank order of relaxant effects of isoproterenol > procaterol > TRK‐380 > salbutamol > BRL 37344. Furthermore, isoproterenol, procaterol and TRK‐380 significantly decreased the amplitude of electrical field stimulation‐induced contractions with a rank order of inhibitory effects of isoproterenol > procaterol > TRK‐380. Conclusions Human ureteral relaxation is mediated by both β2‐ and β3‐adrenoceptor stimulation. β3‐Adrenoceptor agonists have the potential to relax the human ureter, and their clinical application in the treatment of ureteral stones is expected.